2024
DOI: 10.3390/app14072906
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study of the Surface Roughness, Hardness, and Absorption of an Injection-Molded Denture Base Polymer, Manufactured under Insufficient Mold Solidification

Bozhana Chuchulska,
Mariya Dimitrova,
Boyan Dochev

Abstract: The current study sought to investigate the changes in surface hardness, roughness, and moisture absorption of the Vertex ThermoSens polymer (Vertex Dental, 3D Systems, The Netherlands) following immersion in artificial saliva for various periods (7, 14, and 28 days). A total of 60 rectangular specimens with dimensions of 20 mm in length, 20 mm in width, and 3 mm in thickness were made. Due to insufficient mold solidification, these specimens were made utilizing the injection molding process. A Mitutoyo Surfte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…The prevalence of these challenges is underscored by research focusing on implant-retained complete dentures, which has identified fractures of denture teeth as a prominent and persistent concern. This concern is further compounded by the evolving landscape of removable prosthetics, characterized by a rising inclination toward utilizing multiple implants to support prostheses [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of these challenges is underscored by research focusing on implant-retained complete dentures, which has identified fractures of denture teeth as a prominent and persistent concern. This concern is further compounded by the evolving landscape of removable prosthetics, characterized by a rising inclination toward utilizing multiple implants to support prostheses [15,16].…”
Section: Introductionmentioning
confidence: 99%